COMMUNICATION TOPICS AND STRATEGIES IN E-MAIL CONSULTATION: COMPARISON BETWEEN AMERICAN AND INTERNATIONAL UNIVERSITY STUDENTS - Sigrun Biesenbach-Lucas (Language Learning and Technology)
On today's "wired" college campuses, students avail themselves in increasing numbers of electronic channels, most notably e-mail, as a means to consult with their professors. While some research has investigated the purposes for which university students communicate with their instructors via e-mail, little research has examined differences in e-mail use between American and international students. In the present study, e-mail messages sent by American and international students enrolled in a teacher-preparation program to their professor were collected over the course of one semester. The messages were examined for three major communication topics (facilitative, substantive, relational) and communication strategies (requesting, negotiating, reporting). Results indicate quantitative and qualitative differences in American and international students' e-mail topics and strategies, suggesting, similar to findings for face-to-face academic advising sessions, that American students demonstrate greater initiative and ability to adapt to the spatial and temporal remoteness between interlocutors in e-mail interaction, especially when using e-mail to solicit face-to-face appointments and input on projects. Findings also show that messages from both groups of students contained substantial relational communication, perhaps in an attempt to compensate for the lack of visual and paralinguistic clues in the e-mail medium.